2016
DOI: 10.1186/s12864-016-2694-2
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq following PCR-based sorting reveals rare cell transcriptional signatures

Abstract: BackgroundRare cell subtypes can profoundly impact the course of human health and disease, yet their presence within a sample is often missed with bulk molecular analysis. Single-cell analysis tools such as FACS, FISH-FC and single-cell barcode-based sequencing can investigate cellular heterogeneity; however, they have significant limitations that impede their ability to identify and transcriptionally characterize many rare cell subpopulations.ResultsPCR-activated cell sorting (PACS) is a novel cytometry metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 55 publications
(52 reference statements)
0
22
0
Order By: Relevance
“…32 New droplet microfluidic techniques allow this using single-cell PCR, filling a major need, but are challenging to implement due to the requisite complex, multi-step and multi-device workflows. 33 Our results demonstrate an integrated on-chip solution for cell lysis and reagent merger, providing a faster and more reliable method for single-cell droplet RT-PCR.…”
Section: Resultsmentioning
confidence: 71%
“…32 New droplet microfluidic techniques allow this using single-cell PCR, filling a major need, but are challenging to implement due to the requisite complex, multi-step and multi-device workflows. 33 Our results demonstrate an integrated on-chip solution for cell lysis and reagent merger, providing a faster and more reliable method for single-cell droplet RT-PCR.…”
Section: Resultsmentioning
confidence: 71%
“…The FRISCR method[50] has great potential, but relies on suitable antibodies and known cell type markers. Promising alternatives include using fluorescent in situ hybridization or RT-PCR reactions to sort cells on the abundance of mRNA transcripts[58,59], and merging these methods with droplet-based scRNA-seq will be hugely advantageous.In the model of Patch-seq, protocols are sorely needed for sequencing RNA from single cells previously or concurrently characterized by other methods, e.g., physiology, connectivity, developmental lineage, or live imaging. Methods to either maintain[60] or reconstruct[61,62] spatial information in conjunction with scRNA-seq need further development for application to mammalian brain studies.…”
Section: Challenges and Opportunities For Future Studiesmentioning
confidence: 99%
“…The FRISCR method[50] has great potential, but relies on suitable antibodies and known cell type markers. Promising alternatives include using fluorescent in situ hybridization or RT-PCR reactions to sort cells on the abundance of mRNA transcripts[58,59], and merging these methods with droplet-based scRNA-seq will be hugely advantageous.…”
Section: Challenges and Opportunities For Future Studiesmentioning
confidence: 99%
“…18 Subsequent work showed that sorted cells could be pooled and RNA-sequenced to elucidate genome-wide transcriptional changes associated with cancer. 13 Given the flexibility of TaqMan assays, this approach can also be adapted to detect and sort based on alternatively spliced transcripts or the presence of non-coding RNA.…”
Section: Whole Cell Nucleic Acid Cytometrymentioning
confidence: 99%